Penyaluran Bantuan Sosial kepada Para Korban Bencana Alam di Wilayah Ile Ape dan Kedang, Kabupaten Lembata - Bernardus Tube; Marselus Ruben Payong; Yohanes Kurniawan; Polikarpus Payong (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
Community Service Activities by the PkM Team on behalf of the Unika Santu Paulus Ruteng institution along with alumni illustrate concern and a sense of humanity towards others. The Unika Santu Paulus Ruteng Institute was present among the victims of natural disasters in Lembata Regency to ease the burden of their suffering. The presence of the PkM team in social and humanitarian activities, namely distributing and delivering aid directly to victims of natural disasters is a picture of humans as social beings. With the strength of coordination and action, the PkM team demonstrated the presence of the academic community of Unika Santu Paulus Ruteng as a missionary institution that provided relief and consolation for the victims.